An open-label interventional clinical study evaluating sweating function in dupilumab treatment for atopic dermatitis - Mai Matsumoto; Yuta Koike; Motoi Takenaka; Hiroyuki Murota (Journal of Cutaneous Immunology and Allergy)
BackgroundSweat plays a crucial role in maintaining skin homeostasis but is also considered a factor that exacerbates atopic dermatitis (AD). Patients with AD exhibit reduced sweat production and altered sweat composition, with impaired sweating function and psychological anxiety being implicated. However, few clinical studies with high-level evidence have investigated the effects of dupilumab treatment on sweating function and psychological anxiety.MethodsSeven patients with moderate-to-severe AD who received dupilumab treatment at Nagasaki University Hospital were evaluated at baseline, week 6, and week 24. Eczema severity was assessed using the Eczema Area and Severity Index (EASI) score and the Patients’ Oriented Eczema Measure (POEM). Sweating function was evaluated using the Quantitative Sudomotor Axon Reflex Test (QSART), and psychological anxiety was assessed using the State-Trait Anxiety Inventory (STAI).ResultsEASI scores and POEM significantly improved at weeks 6 and 24. Sweat volume assessed by QSART increased at week 6 but showed a decreasing trend in some cases at week 24. Sweat latency shortened at week 6 but was prolonged again in some cases at week 24. State and trait anxiety scores of STAI decreased at week 6 but increased in some patients at week 24. Correlation analysis showed a negative correlation between sweat latency and state anxiety at baseline and a positive correlation between EASI and trait anxiety at week 6. No significant correlations were observed at week 24.ConclusionDupilumab improves skin symptoms in patients with AD and may temporarily enhance sweating function. It also affects psychological anxiety; however, its effects are inconsistent, suggesting individual variations in long-term changes.